Humor dalam Pembelajaran â€œTinjauan Penelitian Humor di Kelasâ€ - Mukhlis, Akhmad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
This article is a summary of research on Instructional humor. The analysis conducted on several journal articles and books to find identification and explain the inconsistencies in the results of research. First, the communication will be reviewed on the basis of humor. This section describes the definition, theory and function of humor in learning both in the psychological perspective and student's academic achievement. Second, an overview of the research results in a quantitative and qualitative perspective. Frequency of use of humor, kind humor and appropriateness for classroom. Lastly, discussions were conducted to see the potential humor and suggestions for teachers in the classroom.